Knowledge, Attitudes and Practices towards Dengue Fever among Attendants of Dengue Fever Patients Admitted at Jinnah Hospital Lahore, Pakistan (Journal of Fatima Jinnah Medical University, 2026)
Background: Dengue fever has a variable clinical presentation and course and causes a significant burden in endemic communities. Understanding people’s knowledge, attitudes and practices (KAP) is essential for monitoring transmission and planning control measures. This study assessed the KAP regarding dengue fever among caregivers of patients admit-ted with dengue fever at Jinnah Hospital, Lahore.Methods: This cross-sectional study was conducted at the Department of Medicine, Unit-III, Jinnah Hospital, Lahore, from January to June 2025. Seventy-three caregivers were enrolled and completed a structured questionnaire assessing knowledge (8 items, score range: 0–8), attitude (8 items, score range: 0–16), and practices (6 items, score range: 0–6). Da-ta were analysed in IBM SPSS version 27. Categorical data were presented as frequencies and percentages, and continuous scores as mean ± standard deviation. Independent-samples t-tests were used to compare scores across age, gender, and educational status, with p < 0.05 considered significant.Results: Knowledge was generally poor (mean 3.14 ± 1.33; 89.0% poor, and 11.0% moderate). Only 27.4% knew dengue spread through mosquito bites, while 47.9% identified the Aedes mosquito as a dengue virus vector. Among them, only 21.9% were aware of the dengue vaccine. Attitudes were also poor (mean 5.78 ± 2.17; 78.1% poor, 21.9% moderate, 0% positive); favourable responses were a minority on every attitude item. Practice scores were modest (mean 3.25 ± 1.23). Knowledge and practice scores were significantly higher among literate participants (p < 0.001), whereas age, gender and all attitude comparisons showed no significant differences.Conclusion: Caregivers demonstrated poor knowledge, poor preventive attitudes, and suboptimal practices regarding den-gue. Educational status was the only factor significantly associated with knowledge and practice. Community-based awareness campaigns and targeted health education are needed.
Keywords: Dengue Fever; Dengue viruses; Knowledge; Practices